Perlindungan Hukum Pemegang Hak Atas Tanah Terhadap Terbitnya Sertifikat Ganda di Kabupaten Sukoharjo - Chandra Handaru Baskara; Purwono Sungkowo Raharjo; Asianto Nugroho (Jurnal Discretie, 2021)
This study aims to determine and examine the legal protection for land rights holders and the factors that lead to the issuance of multiple certificates in Sukoharjo Regency. This research is a prescriptive normative or doctrinal legal research, using a statute approach. The research data was carried out at the ATR/BPN Office of Sukoharjo Regency. Sources of legal materials include primary legal materials and secondary legal materials. the technique of collecting legal materials is document study (library). The technique of analyzing legal materials uses the syllogism method through a deductive mindset. Based on the results of the research, in 2017 Sukoharjo Regency has started the PTSL program which has been started since 2010 through Prona, Proda and PTSL documents in land registration have been completed, so that the target of making Sukoharjo Regency a national pilot object as an Orderly Certificate Regency has been fulfilled. As for legal protection for the community due to land disputes due to the emergence of multiple certificates, the settlement effort by the Sukoharjo Regency BPN is based on the Decree of the Head of the National Land Agency of the Republic of Indonesia Number 34 of 2007 and Technical Instructions Number 05/JUKNIS/DV/2007 on average through mediation. In the case of double certificates due to administrative defects, the settlement efforts by the BPN Sukoharjo Regency based on the Decree of the Head of the National Land Agency Number 11 of 2016 namely revocation and withdrawal of land rights certificates due to administrative defects, so as to create legal certainty for the parties, namely the certainty of subjects holding rights to land rights. land that is entitled and legally on the plot of land. The factors causing the issuance of multiple certificates include: a) ownership of the validity of the database has not been well documented at the Sukoharjo Regency BPN Office, b) self-benefit actions for land owners (community) as an element of intent to re-register certificates, BPN's negligence in implementing management ( bewerken) the land book document, c) the validity of the available information is limited/insufficient for the Base Map Map with the Land Office Computerism (LOC) application, d) the Autocad Map facility that can be used to bewerken the map at the Sukoharjo Regency BPN Office.